Impact of Credit Risk Management on Profitability of Nepalese Commercial Banks (The Harvest, 2023)
This study examines the impact of credit risk management on profitability of Nepalese commercial banks. Default rate, cost per loan assets and capital adequacy ratio are the independent variables used in this study. The dependent variables are return on assets (ROA) and return on equity (ROE). The secondary sources of data have been used from annual reports of selected commercial banks and supervision report of Nepal Rastra Bank. The regression models are estimated to test the significance and effect of credit risk management on profitability of Nepalese commercial banks. The beta coefficient of default rate and cost per assets with profitability (ROA, ROE) has been found negative and statistically significant. The negative sign indicates that there is statistically negative relationship between default rate and cost per loan assets with profitability. Likewise, the beta coefficient of capital adequacy ratio with ROA and ROE is found to be positive and statistically significant. The positive sign of beta coefficient indicates that there is statistically positive relationship between capital adequacy ratio and profitability. The study thus recommends an effective credit risk management for commercial banks of Nepal that maintains an optimum level of capital adequacy ratio, controls and monitors cost per loan assets and balances default rate to enhance financial performance.